2013
DOI: 10.1111/1475-6765.12047
|View full text |Cite
|
Sign up to set email alerts
|

Gender, political participation and electoral systems: A cross‐national analysis

Abstract: This article investigates whether the smaller gender gaps in political engagement, found in more proportional electoral systems, translate into smaller gender differences in political participation. Using data from the Comparative Study of Electoral Systems, it presents the argument that more proportional systems may send signals that multiple interests are included in the policy‐making process, which may increase women's levels of political participation and thereby reduce gender gaps. Additionally, the artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 33 publications
2
29
0
1
Order By: Relevance
“…The concept and phenomenon of a gender gap in political participation, frequently used in contemporary political theory and research (Beauregard, 2018), expresses the difference in the 'proportion of eligible men and eligible women engaging in a particular type of activity' (Glatte and de Vries, 2015: 2). Our results confirmed the ongoing (Coffé and Bolzendahl, 2010;Beauregard, 2014) higher general level of male political participation.…”
Section: Discussionsupporting
confidence: 87%
“…The concept and phenomenon of a gender gap in political participation, frequently used in contemporary political theory and research (Beauregard, 2018), expresses the difference in the 'proportion of eligible men and eligible women engaging in a particular type of activity' (Glatte and de Vries, 2015: 2). Our results confirmed the ongoing (Coffé and Bolzendahl, 2010;Beauregard, 2014) higher general level of male political participation.…”
Section: Discussionsupporting
confidence: 87%
“…From a political point of view, research has shown that institutions play an important role in promoting political equality between women and men (Kittilson and Schwindt-Bayer 2010). In particular, power-sharing political systems favor the involvement of underrepresented groups and therefore women (Beauregard 2014;Kittilson and Schwindt-Bayer 2010). Another explanation for cross-national gender gaps in political engagement is the presence of women in political institutions, with women being more involved in contexts where they have greater descriptive representation (Burns, Schlozman, and Verba 2001;Desposato and Norrander 2009;Reingold and Harrell 2010;Wolbrecht and Campbell 2007).…”
Section: Gender Life Course and Societal Differencesmentioning
confidence: 99%
“…This article investigates cross-national differences in political engagement among European women and men at different stages of the life course. Previous studies have concentrated on betweencountry differences in political involvement on the one hand (Abendschön and Steinmetz 2014;Beauregard 2014;Coffè and Bolzendahl 2013;Desposato and Norrander 2009;Fraile 2014), and on within-country differences in political engagement over the life course on the other (Burns, Schlozman, and Verba 1997;Highton and Wolfinger 2001;Jennings 1979;Stoker and Jennings 1995;Voorpostel and Coffé 2010). The literature currently lacks a large-scale comparative study on the relationship between life course events and women's and men's engagement in politics that could grant us a better understanding of how gender inequalities in politics unfold over the life cycle in different institutional settings.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, a recent study finds that the adoption of quotas can in fact reduce women's political engagement (Clayton, 2015). Yet, more recent cross-national studies report that PR systems are associated with a larger gender gap compared with plurality systems (Beauregard, 2014;Nir & McClurg, 2015). Yet, more recent cross-national studies report that PR systems are associated with a larger gender gap compared with plurality systems (Beauregard, 2014;Nir & McClurg, 2015).…”
Section: Origins Of the Gender Gap And The Impact Of Political Institmentioning
confidence: 93%